Management of cervical atresia and vaginal aplasia leading to hematometra and endometriosis in a young patient: a case report - Lata, Gagan; Nigam, Akanksha; Mittal, Sushil (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Cervicovaginal atresia is a rare congenital anomaly of the female reproductive system where there is a complete absence or severe underdevelopment of the cervix and /or vagina usually presenting in adolescence with severe abdominal pain and primary amenorrhoea which can further lead to endometriosis and pelvic mass. Hereby, we are reporting such a rare case of cervicovaginal atresia in 24 years female who was managed with hysterectomy. Surgery is not strictly required during menstruation, but if there is hematometra, the surgery should be performed as soon as possible to relieve the obstruction. This case reporting aims to offer insights and recommendations for future research on cervicovaginal atresia, ultimately striving to enhance the quality of life for affected individuals.